Healthcare Service Utilization and Awareness of Community Clinics among Ever-Married Women of Reproductive Age in Bangladesh - Md. Nure Alam Siddiqi; Abdul Muyeed (Journal of Community Health Provision, 2022)
The Government of Bangladesh is establishing community clinics to provide essential healthcare services on the doorstep of the citizens of the country. In Bangladesh, women are the most vulnerable group in case of morbidity and mortality, especially in rural areas. They are unaware and underutilize the health care services provided by community clinics. The objective of the present study was to investigate the association of socio-economic and demographic variables with awareness of community clinics and also with the usage of services for health care from these clinics among the ever-wedded women of childbearing age. Bangladesh Demographic and Health Survey (BDHS), 2017-18 data were used in this research study. The study findings reveal that 56% of women who were ever-married were aware of healthcare services provided by community clinics situated in their residential area and 15.6% of women utilized such community clinic services in the 90 days preceding the survey. In this study, by applying bivariate chi-squared (χ2) test, some demographic, social, and economic variables are identified closely associated with consciousness about community clinics and usage of healthcare services from such clinics among women who were aged 15-49 and ever-married. The variables are marital status, educational qualification, working status, type of place of residence, administrative division, the economic condition of the household, ownership of mobile, number of members in the family, and husband’s educational qualification. The government and policymakers should take necessary initiatives to increase the public awareness and utilization of community clinic services. Community clinics should introduce special healthcare facilities for specific groups such as pregnant women or adolescents to increase the utilization of community clinic services.